Worldview in Memoirs «Die Kavaliere von Illuxt» by Alexis von Engelhardt - Talerko, Valentina (Respectus Philologicus, 2021)
The paper is based on the book of memoirs by Alexis von Engelhardt Die Kavaliere von Illuxt, published in 1949. In the territory of Latgale, which is discussed in the book, the Baltic Germans lived in small numbers, therefore the book is of historical, culturological and literary interest. The text of the literary work is understood as an object of scientific reflection; all its components are connected into a single whole by the author’s creative thought. The methodology of the research is based on the interpretation of the literary text, as well as the synthesis of statistical, cultural-historical, semantic and intertextual analysis in the critical perception of the text. The aim of the research is to reveal the worldview presented in the literary work, which consists of the artistic space, representation of time, characters with their functions and objectives, as well as moral and ethical values. The particular objectives of the research include establishing the relationship between the text of the memoirs and jokes and entertaining stories of the Baltic Germans (Pratchen), the features of which have been identified in the author’s previous research, but which still represent a scientific lacuna. On the basis of the life realities described in the book Die Kavaliere von Illuxt it is possible to reconstruct the organization of life of the people that has disappeared from the map of today’s Latvia. The artistic space constructed in this book shows a closed and stagnant world, a lack of impulses for internal development and an appeal to the past. Historical and event-driven artistic time, the inclusiveness of individual stories into the canvas of historical events brings the narrative closer to Pratchen, i.e. jokes and entertaining stories of the Baltic Germans. Alexis von Engelhardt’s book Die Kavaliere von Illuxt is currently the only source of jokes and entertaining stories (Pratchen) of the Baltic Germans about Latgale. The research is funded by the Latvian Council of Science, project The Baltic Germans of Latgale in the context of socio-ethnic relations from the 17th till the beginning of the 20th century, project No.lzp-2020/2-0136.